Non-invasive cardiac output monitoring (NICOM®) can predict the evolution of uteroplacental disease—Results of the prospective HANDLE study. (September 2017) - Monteith, Cathy; McSweeney, Lisa; Breatnach, Colm R.; Doherty, Anne; Shirren, Lucy; Tully, Elizabeth C.; Dicker, Patrick; Malone, Fergal D.; EL-Khuffash, Afif; Kent, Etaoin
Abstract: Objectives: We aimed to firstly identify the different haemodynamic profiles amongst nulliparous women who develop either gestational hypertension (GH), pre-eclampsia (PE), normotensive fetal growth restriction (FGR) versus unaffected pregnancies using non-invasive cardiac output monitoring (NICOM ® ). Our second primary objective was to assess the ability of NICOM ® derived variables to predict the evolution of PE, GH and FGR. Study design: Low risk nulliparous women were enrolled in a single center prospective observational study. NICOM ® assessments were performed at 14, 20 and 28 weeks' gestation and data was obtained on cardiac output (CO), total peripheral resistance (TPR), indexed TPR (adjusted for maternal body surface area; TPRi), stroke volume (SV), indexed SV (adjusted for maternal body surface area; SVi) and heart rate (HR). Logistic regression was used to model GH, PE and FGR with NICOM ® measurements as predictors. Linear, non-linear and interaction terms were assessed using the Akaike Information Criterion. Results: The haemodynamic profile of pregnancies complicated by uteroplacental disease- GH (n = 18), PE (n = 6) and FGR (n = 24) were compared to 318 healthy unaffected pregnant controls. Women with evolving PE have a different haemodynamic profile to those developing either GH or FGR. The best independent predictors for the evolution of uteroplacental disease at 14 weeks' gestation were CO in the prediction of FGR (AUC = 0.61; p 0.002), TPR in the prediction of GH (AUC = 0.63; p < 0.02) and SVi in the prediction of PE (AUC = 0.62; p < 0.05). The performance of haemodynamic variables was enhanced when combined in a multivariate logistic model. We demonstrated that TPR, CO and SV when combined with BP were significant predictors of pregnancies complicated by FGR (AUC = 0.64, p = 0.004; AUC = 0.65, p = 0.004; and AUC = 0.65, p = 0.007 respectively). Whereas in pregnancies complicated by PE, HR and SVi in combination with BP were also statistically significant predictors (AUC = 0.75, p = 0.017 and AUC = 0.77, p = 0.007 respectively). Conclusions: NICOM ® derived maternal haemodynamic profile at 14 weeks' gestation has the novel potential to identify pregnancies which will ultimately develop uteroplacental disease.